2021
DOI: 10.5586/aa.744
|View full text |Cite
|
Sign up to set email alerts
|

An Optimized Micropropagation Protocol by Ex Vitro Rooting of Pear Rootstock OHF 333 (Pyrus communis L.)

Abstract: Pear rootstock OHF 333 ( Pyrus communis L.), which is included in the US ‘Old Home’ × ‘Farmingdale’ series, is characterized by good compatibility with most other varieties, high yields, and a moderate degree of resistance to fire blight. Micropropagation in vitro has shown promise for rapid, large-scale cloning of disease-free plant material throughout the year. However, pear shoots are often recalcitrant to rooting, and this process is highly genotype-dependent. This study aimed to improve the microp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Other researchers have also reported successful acclimatization with various survival rates in a number of Pyrus species, such as 50% up to 83-90% for P. communis [45] and [8] or [43], respectively, 73% for P. pyrifolia [46] and 95% for P. syrica [32]. In a more recent study, Dimitrova et al [47] reported, for P. communis, a faster and better in vitro rooting and acclimatization protocol by using a commercial plant biostimulator of natural origin named Charkor.…”
Section: In Vitro Shoot Rooting and Plantlet Acclimatizationmentioning
confidence: 89%
“…Other researchers have also reported successful acclimatization with various survival rates in a number of Pyrus species, such as 50% up to 83-90% for P. communis [45] and [8] or [43], respectively, 73% for P. pyrifolia [46] and 95% for P. syrica [32]. In a more recent study, Dimitrova et al [47] reported, for P. communis, a faster and better in vitro rooting and acclimatization protocol by using a commercial plant biostimulator of natural origin named Charkor.…”
Section: In Vitro Shoot Rooting and Plantlet Acclimatizationmentioning
confidence: 89%
“…In olives, leaf abscission was accelerated by ABA or ethylene treatment, and the combination of ABA and ethylene treatments showed an effective additive effect in leaf abscission. Abscisic acid can accelerate abscission directly (Estornell et al, 2013;Taylor & Whitelaw, 2001), while some studies suggest that ABA promoting organ abscission depends on interactions with ethylene and auxin (Roberts et al, 2002;Wilmowicz et al, 2016;Dimitrova & Nacheva, 2021). Moreover, ABA can promote abscission through ethylene (Gómez-Cadenas et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, the only effective method of propagation is micropropagation. Since experimenters most often want to regenerate whole plants in in vitro cultures, they are more interested in shoot organogenesis (caulogenesis) than root organogenesis (rhizogenesis) [Dimitrova andNacheva 2021, Kuang et al 2021].…”
Section: Introductionmentioning
confidence: 99%